Dietary hemin promotes colonic preneoplastic lesions and DNA damage but not tumor development in a medium-term model of colon carcinogenesis in rats - de Moura, Nelci A. [UNESP]; Caetano, Brunno F.R. [UNESP]; Bidinotto, Lucas T.; Rodrigues, Maria A.M. [UNESP]; Barbisan, Luis F. [UNESP] (Elsevier, 2019)
Red and processed meat consumption has been strongly related to increase the risk of colorectal cancer (CRC), although its impact is largely unknown. Hemin, an iron-containing porphyrin, is acknowledged as a putative factor of red and processed meat pro-carcinogenic effects. The aim of this study was to investigate the effects of high dietary hemin on the promotion/progression stages of 1,2-dimethylhydrazine (1,2- DMH)-induced colon carcinogenesis. Twenty-four Wistar male rats were given four subcutaneous 1,2-DMH injections and received either balanced diet or balanced diet supplemented with hemin 0.5 mmol/kg for 23 weeks. Colon specimens were analyzed for aberrant crypt foci (ACF) and tumor development. Dietary hemin significantly increased ACF number and fecal water cytotoxicity/genotoxicity in Caco-2 cells when compared to 1,2-DMH control group. However, tumor incidence, multiplicity and cell proliferation did not differ between 1,2-DMH + hemin and 1,2-DMH control group. Gene expression analysis of 91 target-genes revealed that only three genes (Figf, Pik3r5 and Tgfbr2) were down-regulated in the tumors from hemin-fed rats compared to those from 1,2-DMH control group. Therefore, the findings of this study show that high hemin intake promotes mainly DNA damage and ACF development and but does not change the number nor incidence of colon tumors induced by 1,2-DMH in male rats.
Keywords: 1,2-dimethylhydrazine; Aberrant crypt foci; Colorectal cancer; DNA damage; Hemin